The relationship between mobile phone dependence and academic burnout in Chinese college students: a moderated mediator model - Li, Na; Fu, Linxi; Yang, Hewen; Zhao, Wanting; Wang, Xingbo; Yan, Yingchun; Fu, Yangyang (Frontiers in Psychiatry, 2024)
The aim of this study was to examine the correlation between the level of mobile phone dependence among college students and their experience of academic burnout. Additionally, the study sought to explore the potential mediating effect of study engagement and the moderating role of love.During October and December 2023, a cross-sectional study measuring mobile phone dependence, academic burnout, and study engagement among Chinese college students, using the UtrechtWork Engagement Scale-student (UWES-S), College Student Mobile Phone Dependence Questionnaire (CSMPDQ), and Academic Burnout Questionnaire (ABQ). To examine the hypothesis of mediating and moderating effect, SPSS PROCESS was utilized.The predictive effect of mobile phone dependence on academic burnout was significant (β = 0.410, t = 14.236, p < 0.001), and the predictive effect of mobile phone dependence on academic burnout remained significant when the mediating variable study engagement was introduced (β = 0.308, t = 10.288, p < 0.001), mobile phone dependence had a significant predictive effect on study engagement (β = -0.292, t = -11.639, p < 0.001), and study engagement had a significant positive predictive effect on academic burnout (β = -0.270, t = -9.028, p < 0.001). Love significantly negatively predicted study engagement (β = -0.564, t = -9.641, p < 0.001); and the interaction term for mobile phone dependence and love was significant (β = -0.211, t = -3.688, p < 0.001), indicating a significant moderating effect of love between mobile phone dependence and study engagement.Mobile phones among college students has been found to have a direct correlation with academic burnout. It can also indirectly contribute to academic burnout by diminishing levels of academic engagement. This indirect relationship is further influenced by love. These findings can help researchers and educators better understand the underlying mechanisms between smartphone dependence and learning burnout in undergraduates.